International Briefing 7:Training and Development in Singapore - Osman-Gani, A.Ahad M. (Institutional Knowledge at Singapore Management University, 2000)
Singapore's only resource is its people. It has made HRD as a key strategy for economic development since its inception. Its economic success story is entwined with the training and development of its workforce. A national manpower development infrastructure has been put in place to facilitate training and lifelong learning of its people for the twenty-first century under a master plan called Manpower 21. Continuous training and skills development has been possible through close cooperation between the state, employers and the unions through unique working relationships between several policy-making institutions, such as the National Manpower Council and the National Wages Council. [ABSTRACT FROM AUTHOR]